Evaluation of sea turtle handling methods in a captive facility in Nipah, Indonesia - MAISER SYAPUTRA; ENDAH WAHYUNINGSIH; PANDE KOMANG SUPARYANA; ANDI TRI LESTARI; BUDHY SETIAWAN; FAUJIAH NURHASANAH RITONGA (Society for Indonesian Biodiversity, 2025)
Abstract. Syaputra M, Wahyuningsih E, Suparyana PK, Lestari AT, Setiawan B, Ritonga FN. 2025. Evaluation of sea turtle handling methods in a captive facility in Nipah, Indonesia. Biodiversitas 26: 5626-5637. Animal welfare is crucial for sea turtles in captivity and is guided by several principles: freedom from hunger and thirst; freedom from discomfort; freedom from pain, injury, or disease; freedom from fear and stress; and freedom to express natural behavior. The United States Department of the Interior (USDI) Fish and Wildlife Service has issued standard guidelines for handling sea turtles in captivity. This study aimed to evaluate sea turtle conservation efforts through ex-situ strategies by fostering populations in controlled environments. The research was conducted at the sea turtle captive facility on Nipah Beach, Malaka Village, North Lombok District, West Nusa Tenggara, Indonesia, which consists of five rearing ponds and associated facilities where at the time of the research there were 566 individual sea turtles of three species: the olive ridley turtle (Lepidochelys olivacea), hawksbill turtle (Eretmochelys imbricata), and green turtle (Chelonia mydas). Sea turtle handling in captivity was assessed using a scoring method, complemented by observation, measurement, interviews, and laboratory analysis, based on a modified version of the 2019 Captive Sea Turtle Standards issued by the USDI Fish and Wildlife Service, and the key aspects and optimization steps of the captivity were analyzed using Analytic Hierarchy Process (AHP). In conclusion, the management of captive sea turtles achieved an overall score of 369 out of 459 (80.39%), indicating very good conditions. Pond management constitutes the primary determinant in sea turtle captivity, with a value of 0.3049. The priority order of management actions required to optimize sea turtle captivity practices from highest to lowest are: providing pond shading, conducting daily health inspections, regulating pond lighting in accordance with natural daylight cycles, constructing pond edges, and equipping pond lights with covers. Another thing to note is to ensure that there is no overcrowding in the pond. The absence of nationally recognized welfare standards in Indonesia highlights the need for policymakers to establish comprehensive guidelines for sea turtle captivity to ensure consistent and sustainable management practices.